Cambarus polypilosus, a new species of stream-dwelling crayfish (Decapoda: Cambaridae) from the Western Highland Rim of Tennessee, USA - Loughman, Zachary J.; Williams, Bronwyn W. (Zootaxa, 2018)
Cambarus polypilosus sp. nov. is a stream-dwelling crayfish endemic to tributaries in the Buffalo and lower Duck River drainage, and a reach of the lower Tennessee River in the Western Highland Rim of West-Central Tennessee, U.S.A. The new species is closely allied to the three members of the former subgenus Glareocola, but can be differentiated from each by a combination of characters, including body size, coloration, spination, setation, and form I male gonopod morphology. Several meristic measurements and ratios also differentiate C. polypilosus sp. nov. from Cambarus friaufi, to which it is morphologically most similar. Cambarus polypilosus sp. nov. appears to be common in cherty gravel and cobble habitats, where it is typically found in interstices at depths of 0.3 m or more below the substrate surface.